Gabriella Vöő: From the East Looking West: British and Irish Culture and National Self-Definition in Interwar Hungary. Pécs: University of Pécs, Institute of English Studies, 2011. 116 pages. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2012)
The present book is the first volume of a new scholarly series launched by the Institute of English Studies at the University of Pécs. It includes a range of essays addressing the influence of British and Irish literature on the process of cultural modernization in Hungary during the first half of the twentieth century. The discussions focus on the Hungarian reception of individual authors like Oscar Wilde and H. G. Wells, as well as on some broader issues of defining and negotiating Hungarian national identity by referring to aspects of British and Irish cultural history. Despite the once considerable distance dividing the two countries, Great Britain had been an area of interest for Hungarian intellectuals since the late eighteenth century. British culture was valued as a rich storehouse of viable models for literary innovation, and the British parliamentary system of government provided a standard for political modernization in Hungary. The condition of Ireland, on the other hand, seemed to have resonances with the semi-colonial situation of Hungary within the Habsburg Empire. Admittedly, the literary and cultural impact of Britain and Ireland escalated during the interwar period when members of the Hungarian intelligentsia were eager to make attempts to compensate for a perceived cultural backwardness in relation to Western Europe.